Night and day - Parker, Robert B., 1932- (New York : G.P. Putnam's Sons, 2009)
Paradise, Massachusetts, Police Chief Jesse Stone must deal in his own laconic way with the town's rights and wrongs, including a Peeping Town, the Paradise Free Swingers, and a firestorm of protests at the junior high school.
Keywords: Police chiefs -- Massachusetts -- Fiction; Sex crimes -- Investigation -- Fiction; Voyeurism -- Fiction